Implementasi Model 3D Jantung Manusia pada Aplikasi Markerless Augmented Reality - Aldibangun Pidekso Putro; Herman; Muhammad Kunta Biddinika; Suwanti (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Augmented Reality (AR) has become an innovative technology in the healthcare sector. In the medical context, AR offers significant potential, such as supporting medical training, enhancing anatomical visualization, and improving understanding of patient conditions. Cardiac anatomy training and education in the medical world still rely heavily on conventional methods including 2D diagrams, physical models, or desktop-based computer simulations, which are less interactive, inflexible, and less realistic. This research aims to develop a markerless AR application for the visualization of 3D models of the human heart to improve understanding of the heart structure in the context of heart disease treatment. The process starts with the design of a 3D model using Blender, which is then imported into Unity to be integrated with the AR Foundation, allowing the placement of the model in the real world without markers. This AR application was tested on an Android Smartphone device. The test results showed successful visualization of the heart model accurately over the human chest (physical reality). This application makes a significant contribution in medical education by offering an interactive and realistic solution. This research opens up opportunities for the application of AR in health education and medical training. Further development could include interactive features simulating the circulatory system as a whole.